Psychopathy and Occurrence of Gambling Problems: The Role of Gambling Protective Strategies and Urgency. Issue 5 (October 2022) - Kramer, Matthew P.; Peterson, Roselyn; Leary, Angelina V.; Wilborn, Dexter D.; Magri, Tatiana; Dvorak, Robert D.
Background: Psychopathy has been an increasing area of clinical and personality research and is associated with numerous problematic outcomes, including pathological gambling, though this area of research is limited. The most common conceptualization of psychopathy is a two-factor model of primary and secondary psychopathy, with primary psychopathy comprising more interpersonal traits and secondary psychopathy encompassing more antisocial behaviors. Previous research has linked psychopathy to greater urgency and lower utilization of harm reduction strategies. Objectives: The current study examines the relationship between primary psychopathy, secondary psychopathy, and problematic gambling, as well as the possible mechanisms of these relationships. Method: College student gamblers ( n  = 308) completed surveys on psychopathy, impulsivity, protective behavioral strategies regarding gambling, and possible gambling problems. Results: Primary psychopathy was inversely related to gambling protective behavioral strategies (PBS) and secondary psychopathy was positively associated with higher levels of urgency. Secondary psychopathy, via urgency, was a strong predictor of whether an individual will experience gambling problems, while primary psychopathy via PBS better predicts the number of gambling problems one experiences. Conclusion: This study extends an overall under-researched area of gambling and personality and highlights the importance of delineating different factors of psychopathy regarding problematic gambling outcomes.